Hereditary Angioneurotic Edema and Familial Crohn’s Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
A 29-year-old man with Crohn’s disease involving the ileum and cecum was seen. He had angioneurotic edema with C-1’ esterase inhibitor deficiency. Later, his 50-year-old mother was evaluated because of abdominal pain. She had recurrent urticaria, C-1’ esterase inhibitor deficiency and radiographic studies showed Crohn’s disease of the ileum. A maternal family history revealed other members affected with either Crohn’s disease or angioneurotic edema. The clinical observations in this family suggest that angioneurotic edema associated with C-1’ esterase inhibitor deficiency may be closely linked genetically with a familial form of Crohn’s disease.